Pengungkapan Paradigma Lintas Fungsional Sebagai Pemediasi Hubungan Modal Intelektual dan Kinerja Organisasi - Hesti Wahyuni (Jur. Akuntansi, Politeknik Negeri Malang, 2019)
The objective of this research was to examine the impact of Cross functional paradigm, as moderating variable that has not been examined in prior research,to the relationship between Intellectual Capital and organization financial performance. This study was a quantitative research and used Partial Least Square method to examine the hypothesis. The Population is listed company atinfrastructure, transportation and utilities sector,Indonesian Stock Exchanges and used purposive sampling method. This study find that Cross functional paradigmhad negative significantly impact only to the effect of STVA, as one of intellectual capital component, to organization financial performance.